Quality management as a means of improving the company's competitive status - Liang Mugui (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the process of improving the quality management system at the enterprise. The subject of research includes theoretical, methodological, organizational, and practical aspects of improving the quality management system at the enterprise. The purpose of the master's thesis is to summarize the theoretical and methodological foundations and substantiate practical aspects for improving the quality management system at the enterprise. According to the results of the study, theoretical and practical principles were formulated, which the author transformed into specific proposals for improving the quality management system at the enterprise. Practical significance: The research findings are actionable and can be implemented by PJSC KCF "Roshen" to enhance its quality management system. Specific recommendations include refining production processes, adopting advanced quality control technologies, and implementing employee training programs focused on quality improvement.
Scientific advisor: Denchik I., PhD in economics, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; total quality management; management system at the enterprise; principles of the quality management